Penerapan Metode Simpleks Untuk Optimalisasi Produksi Barang Pada UMKM Di Kabupaten Ogan Komering Ulu - Destiarini; Ippy Wimpi (INTECH, 2025)
This study aims to apply the Simplex Method to optimize production levels and maximize profits in Micro, Small, and Medium Enterprises (MSMEs) in Ogan Komering Ulu Regency. The research was conducted to address common challenges faced by MSMEs, such as limited raw materials, labor hours, and production costs, which often result in inefficient resource allocation. The Simplex Method, a mathematical optimization technique used in linear programming, was utilized to determine the optimal number of products to be produced under given constraints. Data were collected through field observations, structured interviews, and production records of selected MSMEs. The analysis revealed that applying the Simplex Method enabled business owners to increase production efficiency by up to 20% while maintaining the same level of resource usage. The study concludes that the Simplex Method can serve as an effective decision-making tool for MSMEs to optimize their production planning, reduce waste, and enhance profitability.